Effects of Bt corn on Rhopalosiphum padi L. (Rhynchota Aphididae) and on its predator Chrysoperla carnea Stephen (Neuroptera Chrysopidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Two years of study on the influence of Bt maize on development of aphids and their interaction with natural predators are reported. Two different experiments were conducted to separate the impact of insecticidal plants on sucking insects from the prey-predators interaction. Laboratory studies determined the effects of feeding com, Zea mays, leaves expressing a Bacillus thuringiensis-derived CrylAb protein on the aphid Rhopalosiphum padi. In turn the predator Chrysoperla carnea was reared on aphids that had fed on transgenic and isogenic corn. No detrimental effects of the transgenic Bt corn on postembryonic developmental time, fecundity or survival of R. padi were recorded. Moreover, no influence on preimaginal development or mortality of C. carnea were observed when reared on R. padi that had fed on Bt corn.
Keywords: Bt com; Rhopalosiphum padi; Chrysoperla carnea; non target effects